IEEE 802.11 Wireless LANs: Performance Analysis and Protocol Refinement - Boucouvalas AC; Chatzimisios P; Vitsas V (EURASIP Journal on Wireless Communications and Networking, 2005)
The IEEE 802.11 protocol is emerging as a widely used standard and has become the most mature technology for wireless local area networks (WLANs). In this paper, we focus on the tuning of the IEEE 802.11 protocol parameters taking into consideration, in addition to throughput efficiency, performance metrics such as the average packet delay, the probability of a packet being discarded when it reaches the maximum retransmission limit, the average time to drop a packet, and the packet interarrival time. We present an analysis, which has been validated by simulation that is based on a Markov chain model commonly used in the literature. We further study the improvement on these performance metrics by employing suitable protocol parameters according to the specific communication needs of the IEEE 802.11 protocol for both basic access and RTS/CTS access schemes. We show that the use of a higher initial contention window size does not considerably degrade performance in small networks and performs significantly better in any other scenario. Moreover, we conclude that the combination of a lower maximum contention window size and a higher retry limit considerably improves performance. Results indicate that the appropriate adjustment of the protocol parameters enhances performance and improves the services that the IEEE 802.11 protocol provides to various communication applications.